2007
DOI: 10.1080/02770900701364304
|View full text |Cite
|
Sign up to set email alerts
|

Associations of BMI, TV-Watching Time, and Physical Activity on Respiratory Symptoms and Asthma in 5th Grade Schoolchildren in Taipei, Taiwan

Abstract: The study evaluated the associations of body fatness, TV-watching time, and physical activity with the occurrences of asthma and respiratory symptoms in schoolchildren in Taipei, Taiwan. A questionnaire survey was conducted to elicit episodes of respiratory symptoms and data on lifestyle and anthropometric factors in 2290 5th-grade schoolchildren. Results show that overweight was positively associated with 5 of the 7 respiratory symptoms. The risk of having respiratory symptoms increased 47%-94% in overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
3
36
1
1
Order By: Relevance
“…Results of this study concerning sedentary behavior and asthma were not in line with several studies that found children spending more screen time were more likely to have respiratory diseases (Arvaniti et al, 2011b;Tsai, Tsai, Nriagu, Gosh, Gong, & Sandretto, 2007). This may be attributed to the younger age included in this study (2-11 years) as compared to Alvaniti et al, It was interesting to note that children ever having asthma differed by age, gender, and poverty; whereas these differences were no longer significant for children currently with asthma.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Results of this study concerning sedentary behavior and asthma were not in line with several studies that found children spending more screen time were more likely to have respiratory diseases (Arvaniti et al, 2011b;Tsai, Tsai, Nriagu, Gosh, Gong, & Sandretto, 2007). This may be attributed to the younger age included in this study (2-11 years) as compared to Alvaniti et al, It was interesting to note that children ever having asthma differed by age, gender, and poverty; whereas these differences were no longer significant for children currently with asthma.…”
contrasting
confidence: 51%
“…Sedentary behaviors, such as television viewing, playing video games, and spending time on the computer have been associated with overweight and obesity (Mitchell et al, 2013). Children spending more screen time (computer, video games, television) were more likely to have respiratory diseases including asthma symptoms (Arvaniti et al, 2011b;Tsai, Tsai, Nriagu, Gosh, Gong, & Sandretto, 2007).…”
mentioning
confidence: 99%
“…Although watching television (TV) and using computers are convenient for discovering the world, spending too much time on these media are associated with disadvantageous behavior and health status (Christakis, Zimmerman, DiGiuseppe, & McCarty, 2004;Hancox, Milne, & Poulton, 2004;Tsai et al, 2007). For instance, watching TV has been linked with attentional problems, being overweight, decreased physical activity, sleep deprivation and unhealthy diet among adolescents, and may represent a preventable cause of childhood obesity (Cheng et al, 2004;Deheeger, Bellisle, & Rolland-Cachera, 2002;Lowry, Wechsler, Galuska, Fulton, & Kann, 2002;Taveras et al, 2006;Tazawa & Okada, 2001;Utter, Scragg, & Schaaf, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it appears that diet may be an important consideration when encouraging adoption of physical activity in adults with asthma. Conversely, higher physical activity levels have been shown to be associated with a decreased risk of respiratory symptoms [61]. Previous research has also shown that a sedentary lifestyle may be associated with higher health care use in adults with asthma [64].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Higher levels of sedentary time, as measured by TV watching time, have been shown to be associated with increased risk of respiratory symptoms in adolescents and children with asthma[61][62][63].…”
mentioning
confidence: 99%